Implementation of The Direct Reading Thinking Activity Model on The Short Story Reading Skills of Fourth Grade Students at Elementary School - Zaqiyah Lailatul Farihah; Siti Hafisyah (IKIP Siliwangi, 2023)
This study aimed to analyze the implementation of the direct reading thinking activity (DRTA) in the short story reading skills of fourth grade elementary school students. This research uses a qualitative approach with a descriptive research type. Data collected by interview, observation, and documentation. The results showed that the implementation of the direct reading thinking activity (DRTA) model was carried out through three stages, namely pre-reading activities, reading activities and post-reading activities. In pre-reading activities, the teacher provides a stimulus by showing pictures and giving clues to the title of short story, so that students can be directly oriented in predicting. In reading activities, the teacher gives freedom to students to read the text and begins to equate with the results of student predictions. In post-reading activities the teacher gives freedom to students to convey the results of predictions about the contents of short story that have been made orally.